WEED SEED BANK IN ARBLE SOIL - Zalihić, Dženisa; Đikić, Mirha; Gadžo, Drena; Gavrić, Teofil (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The weed seed bank is an important source of crop weeding. Knowledge of the weed seed bank is very important for the prediction of weed germination and the proper selection of herbicides. The aim of this research was to determine the weed seed bank in arable soils that were previously used for potato and wheat, and in the plot where alfalfa growing. Soil samples were taken at three different depths: 0 - 10 cm, 10 - 20 cm and 20 - 30 cm. Two methods were applied: physical seed extraction and germination method. A greater number of weed species were identified using the germination method (23), while 19 species were recorded using the physical extraction method. The largest number of weed was recorded in the sample where the previous crop was wheat, followed by alfalfa, and the least after potato.